ISOLASI MIKROBA ENDOFITIK DARI TANAMAN OBAT SAMBUNG NYAWA Gynura procumbens) DAN ANALISIS POTENSINYA SEBAGAI ANTIMIKROBA - Rumella Simarmata; Sylvia Lekatompessy; Harmastini Sukiman (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Sambung nyawa (Gynura procumbens) has many beneficial effects to human health, such as decreasing blood pressure, maintaining blood sugar level (hypoglycaemic), decreasing cholesterol, a remedy for kidney trouble, antibacterial and lessen the inflamation (antiinflamation). This research was undertaken to discover the potency of endophytic microbes from sambung nyawa as antimicrobial agents. The purpose of this research was to screen the endophytic bacteria and the endophytic fungi having antimicrobial activity, which were isolated from stems, leaves, roots and fruits of medical plants, sambung nyawa. The antimicrobial activity was determined by measuring the growth inhibition of pathogenic microbes i.e Candida albicans, Escherichia coli, Pseudomonas sp. and Bacillus subtilis. A total of 38 isolates of bacteria and 15 isolates of fungi were obtained from sambung nyawa. Analysis demonstrated that, 45% isolates of bacteria and 20% isolates of fungi exhibited inhibitory activity. Antimicrobial activity was found in 21% of the isolates that inhibited the growth of C. albicans, E. coli, Pseudomonas sp., and B. subtilis, whereas 24% of isolates had activity only against B. subtilis. Isolate of endophytic bacteria USN 1.1 and USN 2.3 showed the most significant of inhibition zone. The Inhibition zone of the isolate USN 1.1 to C. albicans, E. coli, Pseudomonas sp, and B. subtilis were 2.318 cm2, 0.969 cm2, 0.796 cm2, and 0.381 cm2, respectively. The Inhibition zone of the isolate USN 2.3 to C. albicans, E. coli, Pseudomonas sp., and B. subtilis were 3.01 cm2, 0.519 cm2, 0.588 cm2 and 0.83 cm2, respectively. These results indicated that endophytic bacteria and endophytic fungi could be a promising source for antimicrobial agents.